2002
DOI: 10.1203/00006450-200203000-00017
|View full text |Cite
|
Sign up to set email alerts
|

Oral Bovine Serum Concentrate Improves Cryptosporidial Enteritis in Calves

Abstract: Cryptosporidium parvum produces a prolonged watery diarrhea unresponsive to conventional antimicrobials. Because of reported efficacy of antibody-based immunotherapy, we studied the effect of inexpensive, commercially available oral bovine serum concentrate (BSC) in experimental cryptosporidiosis. Twenty-four calves were treated with 57 g/d BSC (n ϭ 12) or soy protein (n ϭ 12) added to their standard whey protein-based milk replacer (227 g/2 L twice daily). Of the 24, 9 were also treated with L-glutamine (GLN)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
26
0

Year Published

2004
2004
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 49 publications
(29 citation statements)
references
References 30 publications
(32 reference statements)
3
26
0
Order By: Relevance
“…However, shedding was not measured quantitatively and may have been different between diets, but not detectable by the method used. Reductions in diarrhea volume and severity have been previously observed in cryptosporidia-infected calves [15], E. coli-infected pigs [16] and calves [33], and Staphylococcus aureus enterotoxin B-infected rats [34] fed with plasma proteins. In these models of protozoal and bacterial diarrhea, and our viral model of diarrhea, the similar responses observed could relate to a common mechanism despite differences in pathogen and mode of diarrhea induction.…”
Section: Discussionmentioning
confidence: 76%
See 2 more Smart Citations
“…However, shedding was not measured quantitatively and may have been different between diets, but not detectable by the method used. Reductions in diarrhea volume and severity have been previously observed in cryptosporidia-infected calves [15], E. coli-infected pigs [16] and calves [33], and Staphylococcus aureus enterotoxin B-infected rats [34] fed with plasma proteins. In these models of protozoal and bacterial diarrhea, and our viral model of diarrhea, the similar responses observed could relate to a common mechanism despite differences in pathogen and mode of diarrhea induction.…”
Section: Discussionmentioning
confidence: 76%
“…Other studies also have shown that plasma proteins improve intestinal health during pathogen-induced diarrhea. Calves infected with cryptosporidia had greater villus surface area and lactase activity when fed with plasma proteins [15]. Furthermore, E. coliinfected piglets fed with plasma proteins had less histological damage to the intestinal epithelium [16].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Antibody therapy for C. parvum infection has been mainly proposed for persons with AIDS or with other immunodeficiencies. However, studies that have treated a significant number of persons with bovine colostrum from cows that were hyperimmunized with C. parvum oocysts have shown conflicting results (18,22,33,42,43). In light of these findings, the host cell immune response seems to be the only effective form of defense.…”
mentioning
confidence: 99%
“…There is evidence that Ig and other functional components present in SDP and IC are well conserved and are highly functional, providing immunological benefits (46) . For example, they reduce the intestinal inflammation produced by pathogenic bacteria and viruses (47) or by protozoa (48) . The results of our studies on the effects of animal plasma preparations on intestinal inflammation indicate that these supplements can reduce, and in some cases prevent, the inflammatory syndrome induced by SEB.…”
Section: Fig 1 Characteristics Of the Staphylococcus Aureus Enterotmentioning
confidence: 99%